2012
DOI: 10.1177/0269881111434620
|View full text |Cite
|
Sign up to set email alerts
|

Rosiglitazone treatment reversed depression- but not psychosis-like behavior of db/db diabetic mice

Abstract: The objective of the present study was to examine the effect of long-term management of insulin resistance and hyperglycemia on neurobehavioral deficits in db/db mice. In this study, 5-week-old db/db and lean control mice were fed with rosiglitazone (20 mg/kg/day) mixed or standard chow for a duration of 5 weeks. Mice were monitored weekly for blood glucose concentration. Five weeks after the onset of treatment, they were subjected to the forced swim test (FST), pre-pulse inhibition (PPI), open field test (OFT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
27
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(30 citation statements)
references
References 66 publications
3
27
0
Order By: Relevance
“…For instance, rosiglitazone, one of the insulin sensitizers of the thiazolidinedione class, induces an antidepressant-like effect in the tail suspension and forced swim tests in mice, reducing immobilization and floating behavior (Eissa Ahmed and Al-Rasheed, 2009). Similar effects were found for pioglitazone, another insulin receptor sensitizer, which were shown to be NMDA receptor-dependent (Salehi-Sadaghiani et al, 2012; Sharma et al, 2012). Rosiglitazone and pioglitazone were reported to be effective in the treatment of major depressive disorder that was refractory to standard antidepressant treatment and accompanied by insulin resistance (Rasgon et al, 2010; Kemp et al, 2011).…”
Section: Introductionsupporting
confidence: 52%
“…For instance, rosiglitazone, one of the insulin sensitizers of the thiazolidinedione class, induces an antidepressant-like effect in the tail suspension and forced swim tests in mice, reducing immobilization and floating behavior (Eissa Ahmed and Al-Rasheed, 2009). Similar effects were found for pioglitazone, another insulin receptor sensitizer, which were shown to be NMDA receptor-dependent (Salehi-Sadaghiani et al, 2012; Sharma et al, 2012). Rosiglitazone and pioglitazone were reported to be effective in the treatment of major depressive disorder that was refractory to standard antidepressant treatment and accompanied by insulin resistance (Rasgon et al, 2010; Kemp et al, 2011).…”
Section: Introductionsupporting
confidence: 52%
“…Importantly, this depressive phenotype can be reversed by treatment with antidepressive drugs. Previous studies have shown that treating obese, diabetic mice with the insulin sensitizer rosiglitazone, which has been shown to reduce reactive oxygen species formation in the brain (59), can also decrease depressive-like behavior (60). Whether this decrease is through increasing insulin sensitivity in the brain or systemically remains to be determined.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, streptozotocin-treated or db/db diabetic mice exhibit lengthened immobility in the FST, which can be partially reversed by insulin [41]. In addition, rosiglitazone, an anti-diabetic compound improving insulin sensitivity by up-regulation of PI3K/Akt pathway [42], exhibits antidepressant properties in control and diabetic (db/db) mice [43]. However, an alteration of locomotor activity has been observed in these models, limiting the interpretation of the results.…”
Section: Discussionmentioning
confidence: 99%